Complex Adaptive Immunity to Enteric Fevers in Humans: Lessons Learned and the Path Forward - Sztein, Marcelo B.; Salerno-Goncalves, Rosangela; McArthur, Monica A. (Frontiers in Immunology, 2014)
Salmonella enterica serovar Typhi (S. Typhi), the causative agent of typhoid fever, and S. Paratyphi A and B, causative agents of paratyphoid fever, are major public health threats throughout the world. Although two licensed typhoid vaccines are currently available, they are only moderately protective and immunogenic necessitating the development of novel vaccines. A major obstacle in the development of improved typhoid, as well as paratyphoid vaccines is the lack of known immunological correlates of protection in humans. Considerable progress has been made in recent years in understanding the complex adaptive host responses against S. Typhi. Although the induction of S. Typhi-specific antibodies (including their functional properties) and memory B cells, as well as their cross-reactivity with S. Paratyphi A and S. Paratyphi B has been shown, the role of humoral immunity in protection remains undefined. Cell mediated immunity (CMI) is likely to play a dominant role in protection against enteric fever pathogens. Detailed measurements of CMI performed in volunteers immunized with attenuated strains of S. Typhi have shown, among others, the induction of lymphoproliferation, multifunctional type 1 cytokine production, and CD8+ cytotoxic T-cell responses. In addition to systemic responses, the local microenvironment of the gut is likely to be of paramount importance in protection from these infections. In this review, we will critically assess current knowledge regarding the role of CMI and humoral immunity following natural S. Typhi and S. Paratyphi infections, experimental challenge, and immunization in humans. We will also address recent advances regarding cross-talk between the host’s gut microbiota and immunization with attenuated S. Typhi, mechanisms of systemic immune responses, and the homing potential of S. Typhi-specific B- and T-cells to the gut and other tissues.